Killadelphia. Vol. 1, Sins of the father - Barnes, Rodney (Producer) (Image Comics, 2020)
"When a small town beat cop comes home to bury his murdered father--the revered Philadelphia detective James Sangster Sr.--he begins to unravel a mystery that leads him down a path of horrors and shakes his beliefs to their core. The city that was once the symbol of liberty and freedom has fallen prey to corruption, poverty, unemployment, brutality... and vampires. Now, it's up to Jimmy and an unexpected companion to stop long-thought-dead President of the United States John Adams from building an undead army and tsaging a bloody new American revolution."--Page [4] of cover.